2021
DOI: 10.1093/plankt/fbab028
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-specific phytoplankton growth, nutrient utilization and light limitation in the oligotrophic Gulf of Mexico

Abstract: The highly stratified, oligotrophic regions of the oceans are predominantly nitrogen limited in the surface ocean and light limited at the deep chlorophyll maximum (DCM). Hence, determining light and nitrogen co-limitation patterns for diverse phytoplankton taxa is crucial to understanding marine primary production throughout the euphotic zone. During two cruises in the deep-water Gulf of Mexico, we measured primary productivity (H13CO3−), nitrate uptake (15NO3−) and ammonium uptake (15NH4+) throughout the wat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 93 publications
1
24
0
Order By: Relevance
“…The highest 0-100 m integrated NPP was observed in May. Although the float-based 0-100 m integrated NPP (510 mg m À2 day À1 , equivalent to ~42 mmol m À2 day À1 ) was higher than the estimates (24-29 mmol m À2 day À1 ) from the April-May 2017/2018 in situ experiments conducted in the region to the northeast of our research area (Stukel et al 2021, Yingling et al 2021, the shapes of depth profile were similar (Fig. 4a in this work vs.…”
Section: Seasonal Variations Of Surface and Depth-integrated Nppmentioning
confidence: 62%
See 2 more Smart Citations
“…The highest 0-100 m integrated NPP was observed in May. Although the float-based 0-100 m integrated NPP (510 mg m À2 day À1 , equivalent to ~42 mmol m À2 day À1 ) was higher than the estimates (24-29 mmol m À2 day À1 ) from the April-May 2017/2018 in situ experiments conducted in the region to the northeast of our research area (Stukel et al 2021, Yingling et al 2021, the shapes of depth profile were similar (Fig. 4a in this work vs.…”
Section: Seasonal Variations Of Surface and Depth-integrated Nppmentioning
confidence: 62%
“…Satellite-based estimates of surface Chl, bbp, and surface photosynthetically active radiation (PAR surf ) came from Moderate Resolution Imaging Spectroradiometer (MODIS) products, with a spatial resolution of 0.167 by 0.167 and a temporal resolution of 8 days (http://sites.science.oregonstate.edu/ocean.productivity/ 1080.by.2160.8day.inputData.php). The dissolved inorganic nitrogen (DIN; including nitrate and ammonium) profiles were used to help discussing the NPP distribution patterns, because the biological carbon production in the oligotrophic regions is based on both nitrate (new production) and ammonium (regenerated production) (Selph et al 2021, Yingling et al 2021. Since the BOEM floats were not equipped with nutrient sensors, we used the model outputs (monthly climatology from 2012 to 2014) from GoMBio (Gomez et al 2018), a biogeochemical model based on the Regional Ocean Model System, with a horizontal resolution of 8 km and 37 sigma-coordinate (bathymetryfollowing) vertical levels.…”
Section: Study Area and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in a model resolving diel light cycles, uptake of nutrients is possible only during the day. Nutrient uptake by phytoplankton is often found to be significantly higher during the day than at night (Cochlan et al, 1991; Glibert & Garside, 1992; Yingling et al, 2021), hence a Monod model seems relevant to capture the general diel dynamics. However, studies have shown that some phytoplankton continue to take up nutrients during nighttime and store them in internal nutrient pools (Follett, White, et al, 2018; Needoba & Harrison, 2004), and large phytoplankton have significantly larger internal nutrient pools than smaller cells (Marañón et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We assimilated a broad suite of standing stock and rate measurements across multiple trophic levels that included: 466 measurements of NO3concentration and 423 measurements of NH4 + concentration (Knapp et al 2021); 422 measurements each of silicic acid and 84 measurements of biogenic silica (Krause et al 2015;; 455 chlorophyll a measurements (Goericke 2011); 193 measurements of small phytoplankton biomass by a combination of epifluorescence microscopy and flow cytometry (Selph et al 2021;Taylor et al 2012);193 measurements of diatom biomass by epifluorescence microscopy (Taylor et al 2012;Taylor et al 2016);193 measurements of protistan zooplankton biomass by epifluorescence microscopy and/or light microscopy of Lugol's stained samples (Freibott et al 2016); 44 measurements each of vertically-integrated <1-and >1-mm epipelagicresident mesozooplankton biomass; 43 measurements each of vertically-integrated <1-and >1-mm diel-verticallymigrating mesozooplankton biomass; 413 measurements of particulate organic nitrogen and 28 measurements of dissolved organic nitrogen (Stephens et al 2018); 342 measurements of net primary productivity by either H 13 CO3or H 14 CO3uptake methods (Morrow et al 2018;Yingling et al 2021); 149 measurements of nitrate uptake by incorporation of 15 NO3 - (Kranz et al 2020;Stukel et al 2016); 50 measurements of silicic acid uptake by incorporation of 32 Si (Krause et al 2015); 248 measurements each of whole phytoplankton community growth rates and whole phytoplankton community mortality rates due to protistan grazing determined by chlorophyll analyses of microzooplankton dilution experiments (Landry et al 2009;; 53 measurements each of small phytoplankton growth rates and small phytoplankton mortality rates due to protistan grazing determined by highpressure liquid chromatography pigment analyses of microzooplankton dilution experiments combined with flow cytometry and epifluorescence microscopy (Landry et al 2016b;; 53 measurements each of diatom growth rates and diatom mortality rates due to protistan grazing determined by high-pressure liquid chromatography pigment analyses of microzooplankton dilution experiments combined with flow cytometry and epifluorescence microscopy (Landry et al 2016b;; 41 measurements each of verticallyintegrated <1-mm and >1-mm nighttime mesozooplankton grazing rates by the gut pigment method (Décima et al 2016;Landry and Swalethorp 2021); 41 measurements each of vertically-integrated <1-mm and >1-mm daytime...…”
Section: Field Datamentioning
confidence: 99%